Food for future thought: redefining sustainability within agriculture - Madsen, Rainie Marie (Kansas State University, 2021)
In recent times climate change and sustainability have entered the conversation concerning the stability of the future. Current solutions have found ways to continue our disruptive lifestyles by limiting harm and energy consumption but are still not enough. Significant climate change contributing practices such as agriculture will need to be addressed explicitly to prevent the harmful and possibly irreversible effects of climate change and ensure food production safety and reliability for generations to come. Sustainable agriculture practices have been established but given the economic risk, have been made difficult to implement. Even upon adapting these so-called “sustainable practices,” the benefits are not entirely sustainable. The word sustainability has lost its meaning and can often be generalized as just being environmentally friendly, in fact, sustainability needs to be met through various categories. I believe to be truly sustainable; any design should function with economic, environmental, and social sustainability. In proposing a design that encompasses these sustainability categories, I believe the design can be best achieved by fusing new cutting-edge agriculture practices and agritourism. Together the design implementation should create a local food-producing attraction. The design would create local jobs, decrease the need for transportation and fossil fuel dependencies, gain community support, and generate the income for farmers to become more flexible in testing new environmentally safe agriculture practices. In introducing multi-functional programming to sustainable farms, we can draw from current agritourism practices to benefit more than just food production but also the rural communities that host agriculture. In this project, environmentally conscious agriculture practices and agritourism practices are assessed in their ability to work harmoniously in one design for increased benefits. Through a literature review, case study analysis, and a survey of four groups of participants, data collection was compiled and translated into design goals for a series of projective designs. The design projections were applied to a selected site in Wyandotte County, Kansas. The final site design exemplifies a sustainable agritourism park that improves and increases the local economy, community, and environmental factors. Upon completing the design, there was a follow-up focus group who volunteered in the initial survey. The focus group was conducted with the same four categories of participants classified in the survey as: Local policymakers, local traditional producers, local agritourism producers, and potential site design users. The group interview process worked to evaluate the design and projective metrics to create a greater understanding of sustainability, agritourism, and agriculture preconceptions with context of the site. After the focus group process, a final design and site performance metrics were established to set an example design idea for farmers to use as inspiration for making change.
Keywords: Agriculture; Landscape architecture; Climate change; Agritourism; Sustainable agriculture